Chronic kidney disease progression in aged patients - (:unkn) unknown (SPRINGER, 2021)
Purpose Chronic kidney disease (CKD) is a major morbidity, and its prevalence increases with age. However, there appears to be some confusion about the prognosis of CKD in aged patients, because, it has its own characteristics different from youngers. In this study, we investigated the progression of CKD and related factors in aged patients. Methods This was a retrospective study including 334 patients over 80 years of age that were diagnosed with stage 3-4 CKD at our CKD clinic. CKD progression was assessed as an annual decline in the estimated glomerular filtration rate (eGFR). Comorbidities were globally categorized with the Charlson comorbidity index (CCI), but diabetes mellitus, hypertension, and cardiac morbidities were evaluated separately. Patients were grouped as either 'progression to end-stage renal disease (ESRD)' or 'others'. Results During the follow-up period, 191 (57.2%) patients exhibited progression; the annual median eGFR declined by 0.8 ml/min/1.73 m(2). Only 27 (8.1%) of these patients progressed to ESRD. In univariant and multivariate models, respectively, progressing to ESRD was significantly associated with cardiac comorbidities (p < 0.001, p < 0.001), proteinuria (p < 0.001, p = 0.03), and the baseline eGFR value (p < 0.001, p < 0.001). Conclusion In aged patients, CKD progressed slowly, but particularly high initial creatinine levels and proteinuria could be indicator of progression. In addition, cardiac comorbidities may facilitate progression to ESRD.
Keywords: Chronic kidney disease; Progression; Elderly; Factors